2017
DOI: 10.1039/c6nr09495c
|View full text |Cite
|
Sign up to set email alerts
|

p-Type transition-metal doping of large-area MoS2thin films grown by chemical vapor deposition

Abstract: Two-dimensional transition metal dichalcogenides (e.g. MoS) have recently emerged as a promising material system for electronic and optoelectronic applications. A major challenge for these materials, however, is to realize bipolar electrical transport properties (i.e. both p-type and n-type conduction), which is critical for enhancing device performance and functionalities. Here, we demonstrate the transition metal zinc as a p-type dopant in the otherwise n-type MoS, through systematic characterizations of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 75 publications
1
48
1
Order By: Relevance
“…Zn was found to suppress the n-type conductivity in MoS 2 FETs, and its stability and p-type accepter nature was confirmed by DFT calculations (a 2% Zn doping level was found to introduce acceptor states right above the MoS 2 VBE). Moreover, the authors showed a p-type transfer behavior in Zn-doped MoS 2 FETs upon annealing in a sulfur environment, highlighting the importance of sulfur vacancy elimination (recall that native SVs result in unintentional background n-doping of the MoS 2 , as described in Section 3.1) in addition to transition-metal doping for achieving large-area p-type CVD-MoS 2 films [409].…”
Section: Hole Doping By Cation Substitutionmentioning
confidence: 96%
“…Zn was found to suppress the n-type conductivity in MoS 2 FETs, and its stability and p-type accepter nature was confirmed by DFT calculations (a 2% Zn doping level was found to introduce acceptor states right above the MoS 2 VBE). Moreover, the authors showed a p-type transfer behavior in Zn-doped MoS 2 FETs upon annealing in a sulfur environment, highlighting the importance of sulfur vacancy elimination (recall that native SVs result in unintentional background n-doping of the MoS 2 , as described in Section 3.1) in addition to transition-metal doping for achieving large-area p-type CVD-MoS 2 films [409].…”
Section: Hole Doping By Cation Substitutionmentioning
confidence: 96%
“…Intercalation of atoms or molecules in the interlayer space of Mo(S, Se) 2 is one possibility for getting n-type conductivity [84], while substitution of Mo or S(e) inside the layer structure can give both n-type and p-type doping [85]. Experimentally it has been found that Re [86] and Cs [87] give n-type doping while oxygen [88], zinc [89], phosphorous [90], and niobium [91] give p-type doping. This extrinsic doping could be exploited to deliberately optimize the electronic structure of Mo(S, Se) 2 to improve the back contact properties.…”
Section: Electrical Properties Of the Back Contactmentioning
confidence: 99%
“…Previous studies have proved that Raman spectroscopy technology is a powerful tool in determining the doping of TMDCs. [25][26][27][28][30][31][32]35 Fig. 2a is the optical image of asprepared monolayer Sb-doped MoS 2 nanosheet on the SiO 2 /Si substrate.…”
Section: Optical Properties Of Monolayer Sb-doped Mos 2 Nanosheetsmentioning
confidence: 99%
“…20,23,24 Following the theoretical prediction that monolayer MoS 2 would have more interesting physical properties by impurity doping, intensive experimental works have been done on doped monolayer MoS 2 . For example, Zn and Nbdoped MoS 2 crystals exhibit p-type transport properties; 25,26 the optical energy gap of MoS 2 can be controllably modulated by the implant of W and Se atoms; [27][28][29][30] rare-earth Er-doped MoS 2 thin films show up-conversion and down-conversion PL emissions located in near infrared reflection spectral region; 31 additionally, other elements doping of MoS 2 have been also experimentally achieved, such as Co, Re, Cr, V, and Mn. [32][33][34][35] The inhomogenous doping of crystals and the enhanced impurity scattering to electrons hinder the development of elements doping of MoS 2 .…”
Section: Introductionmentioning
confidence: 99%